2018
DOI: 10.22605/rrh4415
|View full text |Cite
|
Sign up to set email alerts
|

Dermatology ECHO - an innovative solution to address limited access to dermatology expertise

Abstract: ABSTRACT:Introduction: The present maldistribution of dermatologists in the USA may make it difficult for patients to access timely and quality care. Access to specialty care may be even more challenging for rural and underserved patients due to geographical limitations and other socioeconomic hardships. With over one-third of primary care patients seeking care for at least one skin problem, it is important to follow the American Academy of Dermatology Special Positioning Workgroup's core areas of impact regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Since its inception, the reach of Project ECHO has expanded beyond New Mexico and the United States 25,27 and has addressed a multitude of conditions beyond hepatitis C. 29-36 Project ECHO has been used to successfully educate primary care clinicians in treating both chronic and acute diseases worldwide by effectively expanding patient access to specialist care and by disseminating knowledge and experience regarding PC to specialists. 25,27…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its inception, the reach of Project ECHO has expanded beyond New Mexico and the United States 25,27 and has addressed a multitude of conditions beyond hepatitis C. 29-36 Project ECHO has been used to successfully educate primary care clinicians in treating both chronic and acute diseases worldwide by effectively expanding patient access to specialist care and by disseminating knowledge and experience regarding PC to specialists. 25,27…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, participants have reported that their participation in Project ECHO is valuable to their practice on many levels. Positive outcomes for patients have also been reported, 29-36 and in the case of hepatitis C, outcomes of the care provided by ECHO-trained, rural primary care clinicians rivaled that of academic medical center specialists. 24 A meta-analysis of publications that investigated Project ECHO concluded that it can be a cost-effective means of improving both provider competence and patient outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Remarkably, rates of sustained virological response were identical in patients treated at UNM and those treated by primary care providers at 21 ECHO sites and dermatology …”
mentioning
confidence: 90%
“…(1) Project ECHO has since proven effective in a number of other medical specialties, including drug addiction (2) and dermatology. (3) In 2011, the Veterans Health Administration adopted the ECHO program to innovate specialty care delivery and renamed it SCAN-ECHO (Specialty Care Access Network-Extension for Community Healthcare Outcomes). The VA Ann Arbor was one of the first to implement SCAN-ECHO for chronic liver disease.…”
Section: See Article On Page 2317mentioning
confidence: 99%
“…Telehealth has multiple benefits for institutions and participants. It reduces travel and time away from work, improves access to consultation and mentoring from experts, facilitates peer-to-peer learning, 32 reduces professional isolation 33 and helps health workers fulfil their CME requirements. 19 Our experience demonstrates the feasibility, scalability and acceptability of this approach in a resource-limited setting and provides a model for other countries.…”
Section: Programme Significancementioning
confidence: 99%